PERKEMBANGAN MUSIK KOREAN POP DI JEPANG DAN PENGARUHNYA TERHADAP GENERASI MUDA JEPANG - SAPUTRA, ADITYA RIZKY; Suyana, Yayan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discusses about the development and influences of K-Pop music through Korean Wave in Japan. K-Pop is South Korean popular culture that is used as a soft power to promote their industry media by South Korean government. K-Pop spreads to Japan after FIFA World Cup 2002 was held in both countries, South Korea and Japan. The purpose of this research is to determine the development of K-Pop music and its influences to Japanese youth in Japan. This research method is descriptive qualitative. It uses the primary and secondary as resources. The primary data is the interview by mail with Japanese respondens, and the secondary data is library search based on books, journals, and internet source. The result of this research is the development of K-Pop music in Japanese music industry. The development happens because of the support from the governments of both countries, medias, industries, and fans. In addition, the respondens of this research who are fans of the K-Pop music explain the influence of K-Pop music in their life. The positive effects are their curiousity about South Korean culture and language are increased and their interest to travel to South Korea are rapidly rose. They also changed their perspective towards South Korea into more positive ways. Then, the negative influence is they become more consumptive and spent a lot of money to buy K-Pop stuffs and attend the concerts. They have also lost their quality times for this reason.